PELAKSANAAN KEGIATAN MBKM KEWIRAUSAHAAN TERHADAP USAHA WOOF TREND’S INDONESIA - Richardo, Fernando; Utama, Louis; Louis, Henrich Moses; Gunawan, Ferry; Han, Clevint Jason (Jurnal Serina Abdimas, 2024)
The implementation of this MBKM examines the development and prospects of the dog clothing business in Indonesia. In recent years, this industry has shown significant growth along with the increasing public awareness of pets as part of the family. This exercise aims to increase attention to fashion in the dog apparel industry, as well as effective marketing strategies in this industry. The results of the exercise showed that the main factors influencing the demand for dog clothing include aesthetics, comfort, and weather protection functions. Effective marketing strategies involve the use of social media for promotion, collaboration with pet influencers, and the development of innovative and high-quality products. This exercise concludes that the dog apparel business has the potential to continue growing in the future. However, entrepreneurs need to understand market dynamics and continue to innovate to meet consumers' needs and wants. Recommendations for entrepreneurs include improving product quality, diversifying designs, and improving customer service to maintain consumer loyalty. ABSTRAK Pelaksanaan MBKM ini mengkaji perkembangan dan prospek bisnis pakaian anjing di Indonesia. Dalam beberapa tahun terakhir, industri ini menunjukkan pertumbuhan yang signifikan seiring dengan meningkatnya kesadaran masyarakat terhadap hewan peliharaan sebagai bagian dari keluarga. Pelaksanaan ini bertujuan untuk meningkatkan perhatian terhadap fashion dalam industri pakaian anjing, serta strategi pemasaran yang efektif dalam industri ini. Hasil pelaksanaan menunjukkan bahwa faktor utama yang mempengaruhi permintaan pakaian anjing meliputi estetika, kenyamanan, dan fungsi perlindungan terhadap cuaca. Strategi pemasaran yang efektif melibatkan penggunaan media sosial untuk promosi, kolaborasi dengan influencer hewan peliharaan, serta pengembangan produk yang inovatif dan berkualitas tinggi. Pelaksanaan ini menyimpulkan bahwa bisnis pakaian anjing memiliki potensi untuk terus berkembang di masa depan. Namun, pelaku usaha perlu memahami dinamika pasar dan terus berinovasi untuk memenuhi kebutuhan dan keinginan konsumen. Rekomendasi untuk pengusaha meliputi peningkatan kualitas produk, diversifikasi desain, dan peningkatan layanan pelanggan untuk mempertahankan loyalitas konsumen.